Pajanan Bising dan Kesehatan Pendengaran di tempat kerja - Lie Tanu Merijanti (Jurnal Biomedika dan Kesehatan, 2022)
Noise exposure is a potential occupational hazard found in almost every industrial sector.In Indonesia from research conducted on workers in workshops, wood industries and ferries, it was found that the noise intensity was between 85 – 103 dB and the prevalence of noise-induced hearing loss was between 21.7% - 34.5%. Besides being able to cause hearing loss, high-intensity noise also causes physical and psychological stress, interferes with communication and concentration, reduces work productivity, and even triggers work accidents. However, noise is often accepted as an unavoidable part of industrial processes causing workers to seem accustomed to noise and do not realize that it will gradually interfere with hearing and if left unchecked it can cause permanent / irreversible sensorineural hearing loss, so preventive measures are the best option to avoid hearing damage.